The role of diffusion MRI in neuroscience. (11th July 2017) - Assaf, Yaniv; Johansen‐Berg, Heidi; Thiebaut de Schotten, Michel; Leemans, Alexander
Abstract : Diffusion‐weighted imaging has pushed the boundaries of neuroscience by allowing us to examine the white matter microstructure of the living human brain. By doing so, it has provided answers to fundamental neuroscientific questions, launching a new field of research that had been largely inaccessible. We briefly summarize key questions that have historically been raised in neuroscience concerning the brain's white matter. We then expand on the benefits of diffusion‐weighted imaging and its contribution to the fields of brain anatomy, functional models and plasticity. In doing so, this review highlights the invaluable contribution of diffusion‐weighted imaging in neuroscience, presents its limitations and proposes new challenges for future generations who may wish to exploit this powerful technology to gain novel insights. Abstract : Diffusion weighted imaging informs about brain regions' structural connectivity and structural connectivity defines brain regions' functional specificity. The application of diffusion weighted imaging in living specimen is also an unique opportunity to study the functional plasticity of the brain.